2021
DOI: 10.3390/ctn5020016
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache Pathophysiology—A Disorder of Network Excitability?

Abstract: Patients’ accounts of cluster headache attacks, ictal restlessness, and electrophysiological studies suggest that the pathophysiology involves Aδ-fibre nociceptors and the network processing their input. Continuous activity of the trigeminal autonomic reflex throughout the in-bout period results in central sensitization of these networks in many patients. It is likely that several factors force circadian rhythmicity upon the disease. In addition to sensitization, circadian changes in pain perception and autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…Many patients describe the pain as localized and sharp [10] and some even liken it to a knife stuck in the head [11]. Several authors thus concluded that this pain feels "escapable" [12] and hypothesized that it is irrelevant for the human brain whether a knife is stuck in the head or if it only feels like there is one: in either case, the affected person engages in an involuntary defence reaction that may feel and manifest like aggression [12,13]. Hence, not seeing another person may prevent directing aggression against them.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients describe the pain as localized and sharp [10] and some even liken it to a knife stuck in the head [11]. Several authors thus concluded that this pain feels "escapable" [12] and hypothesized that it is irrelevant for the human brain whether a knife is stuck in the head or if it only feels like there is one: in either case, the affected person engages in an involuntary defence reaction that may feel and manifest like aggression [12,13]. Hence, not seeing another person may prevent directing aggression against them.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments suggest a reduction of central sensitisation that may help prevent attacks. 82,[84][85][86] The insights that vasoconstrictive agents could end migraine attacks, and that stimulation of serotonin receptors induced vasoconstriction, led to the development of a specific 5-hydroxytyramin agonist. The first one became known as sumatriptan.…”
Section: The Trigeminal-vascular Systemmentioning
confidence: 99%
“…Still, the hypothalamus remains a likely candidate for the ‘ primum movens ’. 84 It is left for future research to explore its role in detail.…”
Section: Insights Into the Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster headache (CH) attacks do not appear randomly throughout the day but happen most often in the hours after midnight and least frequently around noon. 1,2 Although this type of pain is not nociceptive, it seems to implicate the activation of nociceptors-most likely A-delta fibers. 3 Nociceptors signal tissue damage and distention to the brain, which may interpret the input as pain; however, their activation is not equally likely to result in pain at every time of the day.…”
Section: Introductionmentioning
confidence: 99%